2022
DOI: 10.1177/02698811221080462
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selective serotonin reuptake inhibitors on memory functioning in older adults: A systematic literature review

Abstract: Introduction: Selective serotonin reuptake inhibitors (SSRIs) are commonly prescribed to older adults. In contrast to young subjects, it is unclear whether older adults may be vulnerable to cognitive side effects. Serotonin is involved in cognitive functions (e.g. memory). It is of great importance to examine the effects of SSRIs on memory functioning in older adults. Objectives: The objective of this systematic literature review is to summarize studies in which the effects of SSRI treatment on all aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 88 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Some studies have shown that standard antidepressant therapies can improve cognitive function like language memory, working memory, and reaction time in depressed patients 162 . However, a systematic review suggests mixed outcomes, with some studies indicating no significant cognitive effects or even potential memory function harm 163 . In perioperative settings, antidepressant use has been linked to increased POD risk in elderly patients undergoing major joint surgeries, suggesting a potential contribution to the occurrence of PND 164 …”
Section: Interventions Targeting Sd and Their Impact On Pndmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that standard antidepressant therapies can improve cognitive function like language memory, working memory, and reaction time in depressed patients 162 . However, a systematic review suggests mixed outcomes, with some studies indicating no significant cognitive effects or even potential memory function harm 163 . In perioperative settings, antidepressant use has been linked to increased POD risk in elderly patients undergoing major joint surgeries, suggesting a potential contribution to the occurrence of PND 164 …”
Section: Interventions Targeting Sd and Their Impact On Pndmentioning
confidence: 99%
“… 162 However, a systematic review suggests mixed outcomes, with some studies indicating no significant cognitive effects or even potential memory function harm. 163 In perioperative settings, antidepressant use has been linked to increased POD risk in elderly patients undergoing major joint surgeries, suggesting a potential contribution to the occurrence of PND. 164 …”
Section: Interventions Targeting Sd and Their Impact On Pndmentioning
confidence: 99%
“…The risks and benefits of medicines used in the elderly are clearly an important focus of enquiry. Schulkens et al (2022) helpfully add to our knowledge base with a systematic review of the effects of selective serotonin reuptake inhibitors (SSRI) on memory functioning in older adults. Reassuringly, no consistent negative effects of SSRIs on memory functioning in older adults were found after SSRI treatment.…”
mentioning
confidence: 99%